Gambaran Ultrasonografi Pasien Kolelitiasis dengan Perlemakan Hati di RS R. D. Kandou Periode Maret 2023 - Februari 2025 - Kakomore, Keshia Karanina; Memah, Maya Fane; Rondo , Alfa Gracely Einstein Yesuano (Green Publisher Indonesia, 2025)
Cholelithiasis is a common condition with a global prevalence of 6.1% and is often associated with metabolic risk factors that are also found in fatty liver disease. Fatty liver which in this study was determined through ultrasound often coexists with cholelithiasis, particularly in patients with metabolic syndrome. Ultrasound is the primary method due to its accuracy and non-invasiveness. To determine the ultrasound findings of cholelithiasis patients with fatty liver at R. D. Kandou Hospital from March 2023 to February 2025. This study was a retrospective descriptive study with a cross-sectional approach. The sample was obtained using total sampling by including all medical records that met the study criteria. 84 patients with cholelithiasis and fatty liver disease were found to meet the inclusion and exclusion criteria. The majority of patients were female (60.7%) and most were in the 56–65 age group (41.7%). The most common degree of fatty liver disease was mild (65.5%). Based on gallstone characteristics, most patients had a single stone (54.8%) and a stone size ?10 mm (53.6%). Patients with cholelithiasis and fatty liver were predominantly female, aged 56–65 years, had mild fatty liver, a single stone, and a stone size ?10 mm.